Sediment dynamics and tidal inlet relocation in mixed-energy settings: the case of Ancão inlet (Algarve - Portugal) - Concejo, Ana Vila (2003)
The main aim of this thesis is to study the sedimentary dynamics of mixed energy tidal inlets on different time scales (from hours to decades) as well as to analyse inlet relocation as a coastal management tool. The field studies were carried out in the Ria Formosa, a multi-inlet barrier island system located in southern Portugal. Long Term Studies: The four natural inlets of the Ria Formosa were studied for the period between the 1940’s and 1996. Inlet width and position of the inlet channel were determined using a series of vertical aerial photos and charts. The objective was to determine the association between inlet migration patterns and different hydrodynamic conditions, major storms and engineering interventions. Results indicate that natural inlet opening and evolution were mainly affected by three factors: (a) the existence of sub-embayments (western and eastern) inside the system, (b) exposure to wave energy, and (c) inlet efficiency. Two distinctive eastward migration patterns were found by analysing the correlation coefficient (r) between inlet width evolution and inlet migration and by the comparison of the shape of the curves fitted to the inlet migration behaviour. Typical migration of the high-energy flank is characterised by an initial stage of readjustment, with low migration rates, followed by a stage of high eastward migration rates, up to a limiting position. Inlet width remains reasonably constant during the entire migration cycle, thus the correlation between inlet width and position is very low. Typical inlets on the low-energy flank are formed by barrier breaching during major storms and produce, initially, very wide inlets. Eastward inlet migration on the low-energy flank follows a natural logarithmic curve where channel migration is accompanied by strong constructional processes on the updrift barrier. Due to subsequent inlet width reductions, the correlation between inlet width and position is significant. Medium Term Studies: A monitoring program, including the acquisition of a series of topo-bathymetric surveys and oblique aerial photos, has been carried out at Anc˜ao Inlet since its artificial opening in June 1997. The results (morphologic and volumetric) were analysed with relation to the prevailing oceanographic conditions. This allowed the development of a conceptual evolutionary model for the natural evolution of artificially opened inlets with 4 stages: Stage 1 is the artificially opened inlet; Stage 2 represents the inlet after reaching dynamic equilibrium for the channel and while it is developing the deltas; Stage 3 is the mature migrating inlet; and Stage PS (Post-Storm) is the inlet situation after high-energy conditions. Transition between stages 1 to 3 is a continuous process with intermediate sub-stages. Transition to Stage PS is a discrete phenomenon, caused by high-energy events, after which the inlet continuously changes back to the previous stage. Short Term Studies: Three sediment transport studies using tracers were performed at Anc˜ao Inlet. The objectives of the experiments were to determine and understand the sediment transport pathways and magnitudes on the updrift margin of an inlet. In order to apply the traditionally used Space Integration Methodology to the tracer experiments, some adaptations had to be made. The division of the study area into morphologically defined sectors was found to be a key factor for the applicability of tracers in such a complex area. Therefore, 4 sectors were defined: Sector A representing the straight part of the updrift beach; Sector B being the upper area of the swash platform; Sector C being the lower area of the swash platform; and Sector D representing the inner parts of the inlet margin. The integrated study of all data (wind, waves, currents, tracer distribution and topographic evolution) led to the determination of the sediment pathways. Three tidal stages (TS), associated with distinctive sediment transport patterns, were found to occur at the inlet margin during each tidal cycle: TS1 implies flooding currents, and thus, transport towards the inside of the inlet area, both on the swash platform and the inner parts of the inlet area; during TS2 flooding currents transporting sediments towards the inlet occur on the swash platform whilst the interaction of the flooding currents with the flood delta produces the development of an anticlockwise internal gyre (IG) that results in ebbing currents occurring in the inner inlet margin; TS3 implies ebbing transport both in the inner margin and the swash platform. Evidence of the existence of a clockwise external gyre (EG) on the swash platform was found. A semi-quantitative conceptual model was developed in order to explain the sediment transport pathways and magnitudes that a known mass of sediment would follow after arriving at the swash platform. It was found that the areas with the largest sediment accumulation were Sector B and C, whilst almost no sediment was retained in Sector D which underwent strong erosive processes. According to the model only 48% of the initial mass of sediments are still in the system after two tidal cycles. It is hypothesised that sediment losses are due to sediment transport towards the ebb delta and to sediment by-passing occurring from the ebb delta to the downdrift beach through swash bar processes. The herein defined conceptual model represents a useful tool that could be applied to other tidal inlets under similar conditions, facilitating sediment budget studies around tidal inlets. Inlet Relocation Assessment: Two inlets were relocated in the Ria Formosa and were the subject of a monitoring program that included the acquisition of quantitative (topo-bathymetric surveys) data. The data obtained from the monitoring program were analysed together with the wave climate and then compared with historical information on the natural inlets, in order to assess the degree of success of the relocation actions. One of the relocations studied, Anc˜ao Inlet, was considered to be successful even though an initial unexpected behaviour produced some material damage to property. On the contrary, the relocation of Fuzeta Inlet, did not have the expected results and the new inlet was effected by the same problems as the old one. It was found that the most important factor for a relocation action to succeed is the correct choice of the location of the opening. A theoretical procedure to enhance the possibilities of relocation success is suggested: (1) Hydrodynamic studies are needed in order to determine if the present conditions are similar to the historical ones. (2) The position for the inlet opening is chosen according to the hydrodynamic conditions but there are other factors to be taken into account, i.e., the historical migration paths and typical inlet width of the natural inlet; the hydrodynamics of the backbarrier; the morphology of the backbarrier and, for multi-inlet barrier island systems, the proximity to adjacent inlets. (3) Once the position is chosen, environmental impact studies should be made in order to assess the risk of the relocation for the ecosystems of the area. Only if the environmental impact studies are favourable, should a relocation action be performed.